Attitudes Towards Seeking Psychological Help Among Community Dwelling Older Adults Enrolled in Primary Care in Chile - Moreno-Herrera, F (BioMed Central Ltd, 2024)
Background: Depression and anxiety are common mental disorders among older adults, but they are frequently underdiagnosed. Attitudes towards seeking professional mental health care is one of the barriers to access to treatment. This study was aimed at assessing the attitudes towards seeking psychological help among older adults who are enrolled in primary care in Chile, and to determine the associated factors. Methods: This cross-sectional study recruited 233 primary care users aged 65 or more years. The Attitudes Towards Seeking Professional Psychological Help was used. Reliability and factor analysis of this scale were carried out. The average scores of the scale and factors were calculated and compared, by selected variables. Multivariate linear regression was estimated to determine factors associated with attitudes towards seeking psychological help. Results: Three factors were identified in the attitudes towards seeking psychological help: confidence in psychologists, coping alone with emotional problems, and predisposition to seek psychological help. On average, participants had a favorable attitude towards seeking psychological help, compared with previous research. Lower level of education, and risk of social isolation were inversely associated with these attitudes. Conclusion: Strategies to improve mental health literacy and social connection among older adults, could have an impact on factors that mediate the access to mental health care, such as attitudes towards seeking psychological help, among people who have a lower level of education or are at risk of social isolation. © The Author(s) 2024.